Mathematical Model of Cam Profile Based on Heald Frame Motion Characteristics. (19th February 2020) - Yin, Honghuan; Yu, Hongbin; Peng, Junqiang; Shao, Hongyu
Abstract : In this paper, the transmission process of the heald frame driven by the dobby is analyzed. The equivalent motion model of the dobby modulator, the eccentric mechanism, and the motion transmission unit are constructed. Then, based on the given movement characteristics of the heald frame, the mathematical model is built to achieve the cam pitch curve and the cam profile of the modulator. The numerical solution method for this is developed. The preparation of a mathematical model for the new concept of the solving cam profile based on the motion characteristics of heald frames is explained in this study. By setting a 11 th polynomial motion law of the heald frame, due to the inconsistency between the outward and return motion laws of the crank-rocker mechanism, an asymmetrical cam profile is obtained under the premise of ensuring that the heald frame's ascending and descending motions are consistent. Through the kinematics simulation analysis, the correctness of the reverse process is verified.